2018
DOI: 10.1242/jcs.209122
|View full text |Cite
|
Sign up to set email alerts
|

SOD1A4V aggregation alters ubiquitin homeostasis in a cell model of ALS

Abstract: A hallmark of amyotrophic lateral sclerosis (ALS) pathology is the accumulation of ubiquitylated protein inclusions within motor neurons. Recent studies suggest the sequestration of ubiquitin (Ub) into inclusions reduces the availability of free Ub, which is essential for cellular function and survival. However, the dynamics of the Ub landscape in ALS have not yet been described. Here, we show that Ub homeostasis is altered in a cell model of ALS induced by expressing mutant SOD1 (SOD1). By monitoring the dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 81 publications
2
29
0
Order By: Relevance
“…A major disadvantage of immunodetection using either affinity epitopes or endogenous epitopes is that this requires the fixation of cells, making it challenging or impossible to analyze dynamic events. Combined usage of both fluorescent tagging and FRAP has revealed that specific aggregation-prone proteins can localize to distinct inclusion types (Kaganovich et al, 2008 ) and that the mobility of SOD1, TDP-43, and FUS in and outside inclusions and other compartments can be examined using photobleaching (Matsumoto et al, 2005 , 2006 ; Weisberg et al, 2012 ; Farrawell et al, 2015 , 2018 ; Park et al, 2017 ).…”
Section: In Vitro Models To Examine Proteostasis and Prion-lmentioning
confidence: 99%
“…A major disadvantage of immunodetection using either affinity epitopes or endogenous epitopes is that this requires the fixation of cells, making it challenging or impossible to analyze dynamic events. Combined usage of both fluorescent tagging and FRAP has revealed that specific aggregation-prone proteins can localize to distinct inclusion types (Kaganovich et al, 2008 ) and that the mobility of SOD1, TDP-43, and FUS in and outside inclusions and other compartments can be examined using photobleaching (Matsumoto et al, 2005 , 2006 ; Weisberg et al, 2012 ; Farrawell et al, 2015 , 2018 ; Park et al, 2017 ).…”
Section: In Vitro Models To Examine Proteostasis and Prion-lmentioning
confidence: 99%
“…Mutations in UPS-associated genes have been shown to cause ALS, including the E3 ubiquitin ligase CCNF [13], UBQLN2 [14], VCP [15] and SQSTM [16]. Altered Ub distribution has been observed in ALS models [17], and mutations in the key UPS regulator ubiquitin-like modifier activating enzyme 1 (UBA1) cause the juvenile motor neuron disease, spinal muscular atrophy (SMA) [18,19]. Conversely, increased expression of UBA1 has been shown to attenuate the disease phenotype of SMA in mouse and zebrafish models [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The pervasive use of ubiquitin and ubiquitin-like protein modifications in both genome maintenance and protein homeostasis mechanisms has led to the idea that under proteotoxic stress, the PQC network competes for free ubiquitin with other ubiquitindependent processes, including genome maintenance and chromatin regulation pathways (Dantuma et al 2006;Park and Ryu 2014). In line with this, proteasome dysfunction and aggregation of ubiquitin-positive substrates have been shown to specifically deplete the nuclear pool of unconjugated ubiquitin (Farrawell et al 2018;Mimnaugh et al 1997), and one recent study reported that DNA repair capacity was hampered as a consequence of this (ben Yehuda et al 2017). However, mechanistic intervention studies are lacking so far, and although ubiquitin-, NEDD8-and SUMOconjugated substrates all accumulate in protein aggregates upon proteotoxic stress (Bence 2001;Enchev et al 2015;Liebelt and Vertegaal 2016), it is still unclear if competition for these posttranslational modifiers can explain increased genomic instability upon a loss of protein homeostasis.…”
Section: The Pqc Network Is Crucial To Maintain Genome Integritymentioning
confidence: 99%